Impact of Protoporphyrin Lysine Derivatives on the Ability of Nosema ceranae Spores to Infect Honeybees - Katarzyna Buczek; Kamil Deryło; Mateusz Kutyła; Katarzyna Rybicka-Jasińska; Dorota Gryko; Grzegorz Borsuk; Beata Rodzik; Mariusz Trytek (Insects, 2020)
The effect of two protoporphyrin IX derivatives conjugated with single (PP[Lys(TFA)-OH)]2) or double (PP[Lys(TFA)-Lys(TFA)-OH]2) lysine moieties on the infectious capacity of Nosema ceranae spores was examined, and their efficacies were compared with those of a cationic porphyrin (H2TTMePP). Honeybees were inoculated with spores preincubated with porphyrins or with untreated spores (control). A significantly lower level of infection was observed in the bees infected with the porphyrin-treated spores than in the infected control. Porphyrins 1 and 2 reduced the infectious capability of microsporidia more efficiently than porphyrin 3, with bee mortality declining to almost 50%. Confocal analysis of the midguts of infected bees revealed distinct differences in the number of spores between the control group and the group infected with PP[Lys(TFA)-Lys(TFA)-OH]2-treated spores. Notably, bees with a reduced level of infection consumed less sucrose syrup than the control bees, indicating a reduction in digestive disorders and an improvement in food absorption.